The Environmental Policy of the USA in the Framework of the Kyoto Protocol and Paris Climate Agreement Before Biden's Administration - Ayvaz, Zehra; Ramadhan, Jelang (LPPM Universitas Lampung, 2023)
Despite different kinds of “habitat” research (Moon, Mars, etc.) has accelerated, the Earth is still actually the only habitat for living creatures. However, due to developments in the last century, our world has faced various environmental problems and dangers like climate change. So, countries carry out national and international efforts to minimize and prevent these hazards. One of the countries that researches these problems is the United States. The fact that the United States, the most powerful actor in the international system, has not shown sufficient interest in environmental and climate change issues and that US domestic policy has largely had an impact on these issues, contributed to preparing this study. The paper used qualitative research design by emphasizing literature study and a descriptive method to measure the trend in perceiving climate change from the perspective of the US policy. So, in this study, the US Environmental Policy will be discussed in the context of the Kyoto Protocol and the Paris Agreement before Biden's Administration which resulted in Washington cannot take a clear stance on environmental and climate issues due to dilemmas in leadership change and domestic politics.